Freeze-Thawed PVA Hydrogel Loaded by Morinda Citrifolia L. Leaves Extract with Physical and In-Vitro Antibacterial Properties - Kusjuriansah, Kusjuriansah; Mufti, Ade; Nilva Tulhana, Fauzah; Fauziah, Dinny (Jurusan Fisika FMIPA Universitas Andalas, 2025)
Morinda citrifolia L. leaves extract (MCLE) has been used as a medical material because of its antibacterial properties. Hydrogels synthesized from polyvinyl alcohol (PVA) are known to be applicable as delivery media for antibacterial substances. This article reports using the freeze-thaw method to use PVA hydrogel as an encapsulation medium for MCLE. PVA/MCLE hydrogel was synthesized in several combinations, namely 10:0, 10:1, 10:2, 10:3, 10:4, and 10:5. The test results showed the conductivity and pH values of the precursor solution ​​increased as the extract fraction increased, but decreased in the viscosity. The hydrogel showed a morphology with increased pore size when the extract fraction in the hydrogel increased. FTIR characterization confirmed that the extract had been successfully loaded into the hydrogel. The swelling degree test of the hydrogels showed an increase for samples 10:1 to 10:3 and a decrease for samples 10:4 to 10:5. Increasing the extract fraction then resulted in a decrease in the gel fraction of the hydrogel. The antibacterial activity test confirmed that the antibacterial activity in the extract remained present after being encapsulated in the hydrogel. Thus, the addition of MCLE affects the performance of the hydrogels to be applied in the medical field.